ANALISIS NILAI TAMBAH DAN FINANSIAL USAHA PENGOLAHAN IKAN LELE (Studi Kasus Pada Poklahsar Winaka Kecamatan Kota Gajah, Kabupaten Lampung Tengah) - Sari, Septi Permata; Zakaria, Wan Abbas; Murniati, Ktut (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2020)
The purposes of this research are to analyze the added value and the financial feasibility of the business. This research was conducted at the Poklahsar Winaka in the Kota Gajah Subdistrict, Central Lampung Regency. The location was chosen purposively with the consideration that Kota Gajah Subdistrict is a center of catfish production and Poklahsar Winaka is the only catfish processing business in the Kota Gajah Subdistrict. The first goal was analyzed with Hayami’s method, and the second used financial feasibility criteria. The results showed that the added values of the products produced in Poklahsar Winaka was IDR21,476.95 per kg of raw materials on catfish meatball product, and IDR23,614.82 per kg of raw materials on catfish nuggets. Poklahsar Winaka business was profitable and feasible to continue and develop. Key words: added value, agroindustry, business feasibility